REGIONAL DIMENSION OF CHANGES IN BULGARIAN AGRICULTURAL STRUCTURE - R. Beluhova-Uzunova; M. Shishkova; K. Hristov (Trakia Journal of Sciences)
Agriculture is an important sector in Bulgaria, especially in the rural areas where it is considered an important source of income and employment. Bulgarian agriculture has changed substantially over the past ten years, which has led to a transformation in production, farm, organizational and sectorial structures. The aim of the paper is to observe the regional differences in Bulgarian farm structure and outline main prospects for the next programming period, 2023-2027. The survey reveals a significant decline in the number of holdings in parallel with the decreased role of small farms. By contrast, the importance of large holdings is increasing. There are different patterns of agricultural transformation in the regions of Bulgaria. While large extensive producers dominate North Bulgaria, there is more balanced agricultural development in the South part of the country. The new CAP 2023-2027 is directed to more ambitious objectives related to climate, innovations and convergence. The subsidiarity principles could help Bulgaria to overcome some of these challenges if the agricultural policy is better targeted and oriented towards intensive sectors and more balanced and sustainable rural development.